Agranulocytosis Associated with Topiramate: A Case Report and Review of Published Cases - Saroj Lohani; Niranjan Tachamo; Salik Nazir; Anthony Donato (Case Reports in Hematology)
A 41-year-old female presented to the hospital with sore throat and shortness of breath. She was hypoxic with an oxygen saturation of 87% in room air. Physical examination revealed swollen uvula with exudates. She had been started on topiramate for treatment of migraine few months ago. The dose of topiramate was increased to 100 mg twice daily 2 weeks ago. Complete blood count revealed an absolute neutrophil count (ANC) of 8 c/mm3. She was intubated and started on broad-spectrum antibiotics. She was transferred to our hospital on the fifth day of hospitalization. On arrival, her absolute neutrophil count was 10 c/mm3. Her agranulocytosis was attributed to topiramate after ruling out other possible causes. ANC improved after topiramate was stopped. ANC increased to 1000 after 5 days of stopping topiramate. We also reviewed published cases of topiramate-associated agranulocytosis. Agranulocytosis is a rare side effect of topiramate, and only 3 case reports have been published so far. In all cases, agranulocytosis developed after months of topiramate therapy and when dose was increased to 200 mg daily suggesting a dose-dependent effect. Next steps would be further research on the pathogenesis of agranulocytosis associated with topiramate and creation of registry for data synthesis.